Reducing Students' Speaking Anxiety through Video Self-Recording in Speaking Class at UIN Sayyid Ali Rahmatullah Tulungagung - Anindita Badianti (Civiliza Publishing, Indonesia., 2026)
Speaking anxiety is one of the major challenges faced by English as a Foreign Language (EFL) students, often affecting their confidence, participation, and speaking performance. This study aimed to investigate the effectiveness of Video Self-Recording (VSR) in reducing students’ speaking anxiety in speaking classes at UIN Sayyid Ali Rahmatullah Tulungagung. Employing a Classroom Action Research (CAR) design, the study involved undergraduate students enrolled in a speaking course and was conducted through two cycles of planning, acting, observing, and reflecting. Data were collected through speaking anxiety questionnaires, classroom observations, interviews, reflective journals, and speaking performance assessments. The findings indicated that Video Self-Recording significantly reduced students’ anxiety levels, enhanced their self-confidence, increased their willingness to communicate, and improved their speaking performance. Students benefited from the opportunity to practice repeatedly, evaluate their own performances, and reflect on areas for improvement in a less stressful environment. The study concludes that Video Self-Recording is an effective technology-assisted learning strategy that promotes learner autonomy, self-reflection, and confidence while helping students overcome speaking anxiety in EFL speaking classrooms.